Bilosome Nanocarriers for Enhanced Oral Bioavailability and Cardiovascular Activity of Milrinone - Santhinathan, Kiruthika; Durai, Susmitha; Sirajudeen, Rijivana; Govindhraji, Gopinath; Gopal, Saravanan; Kumararaja, Gayathri (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Cardiovascular Diseases (CVDs) are the main causes of death in both industrialized and developing nations, which are mostly brought on by poor lifestyles and insufficient physical activity. Recent years many novel approaches have been developed for effective drug delivery of cardiovascular drugs. Milrinone [MRN] is a cardiovascular medication that is mainly used in the intensive care unit and cardiac unit to provide cardiac support to patients suffering from acute heart failure. It is also used to wear patients who have pre-existing left ventricular dysfunction from cardiopulmonary bypass, or it can be used as a temporising agent for patients awaiting heart surgery or transplantation. Milrinone is poorly water soluble and milrinone salt was used in the market. Aims: This work aimed to develop; a bilosome carrier was used to enhance the bioavailability of MRN. Materials and Methods By using thin film hydration method the MRN Bilosomes were prepared. Results: The formulation shows spherical morphology by SEM image and particle size were found to be 120 nm±6.8. The formulation was stable which shows -37.2±2.3 mV of zeta potential. The drug release was 88±1.3% with the Entrapment efficiency of 81±1.7% w/w. Cellular uptake and cell viability studies were carried using H9c2 cells. Flowcytometry technique was used for cellular uptake study. The results indicate the fluorescence seen for the uptake of MRN-bilosomes by the cells. The MTT assay indicates there was 2-fold increases in cell viability of MRN-bilosomes when compared to milrinone lactate. Conclusion: These findings suggest that MRN bilosomes were effective against cardiovascular disease with increased bioavailability.
Keywords: Milrinone; Bilosomes; Cardiovascular Disease; H9c2 Cells; Cellular Uptake Study